RESULTS OF APPLYING A BURNOUT CORRECTION PROGRAM FOR MILITARY PERSONNEL OF THE ARMED FORCES OF UKRAINE - Mykolaichuk, Olena (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . A theoretical and methodological analysis highlights the necessity of integrating preventive, administrative, and personalityoriented measures aimed at reducing the impact of stress factors and enhancing the overall psychological resilience of military personnel. Addressing and preventing professional burnout, a multidimensional construct that combines a range of psycho-emotional states of negative modality and destructively affects ability of military personnel to fulfill their professional duties, requires a systematic approach. The purpose of this article is to theoretically substantiate and experimentally investigate the impact of a burnout correction program on the Armed Forces of Ukraine military personnel under conditions of a full-scale invasion. M e t h o d s . The study employed both theoretical methods (analysis, comparison, generalization, systematization) and empirical methods, namely: the Burnout Assessment Tool (BAT), Maslach Burnout Inventory (MBI), methods of mathematical statistics. R e s u l t s . A diagnostic experiment identified the levels and intensity of professional burnout among combatants. The effect of the correctional program on the formation and manifestations of burnout syndrome was analyzed. A strong correlation was found between the components of professional burnout and personality traits of both positive and negative valence, the changes in which influenced the psycho-emotional state and mental health of combatants. C o n c l u s i o n s . A comparative analysis of professional burnout indicators before and after the program’s implementation was conducted. Positive dynamics in personality traits were observed, indicating improvements in respondents’ psycho-emotional state. The effectiveness of the developed burnout correction program for military personnel of the Armed Forces of Ukraine was demonstrated. The importance of implementing the program in military units is emphasized to balance combatants’ emotional state, reduce manifestations of professional burnout, or prevent its onset, which represents a long-term investment in professional efficiency and mental health.